China’s Highly Educated Talents in 2015: Patterns, Determinants and Spatial Spillover Effects - Gu, Hengyu; Meng, Xin; Shen, Tiyan; Wen, Luge (Applied spatial analysis and policy, 2020)
Using data from the 2015 national one percentage population sample survey, this paper examines the distribution, driving forces, and spatial effect of highly educated talents at the prefecture level. It involves spatial autocorrelation analysis and spatial econometrics models. The results show that the spatial pattern of talents is highly concentrated, unbalanced, and clustered among cities. Economic opportunities are the main forces affecting the distribution of talents, although some amenity variables (e.g., public services and accessibility) also matter. Our findings suggest that spatial spillover effect of the distribution of talents mainly comes from the influence of cross-city or country specific talent policies and social network linkages.